Critical success factors for soft TQM and lean manufacturing linkage - Khalili, Amjad; Ismail, Md Yusof; Karim, Ahmad Izwan Mustafizul; Che Daud, Mohd Radzi (Hashemite University, 2017)
Implementation of Total Quality Management (TQM) and Lean Manufacturing (LM) is a common goal for manufacturers to be leaner. While many studies have investigated TQM and LM separately, the present paper explores the Critical Success Factors (CSF) for these practices together in one model focusing on the soft dimension of TQM. A structured closed questionnaire was distributed to operations managers in Malaysian industries. A 5-point Likert scale was used in designing the survey questionnaire. One hundred and two responses were collected in this preliminary study. Results obtained through Principal Component Analysis (PCA) showed that both latent contracts are reliable. Both KMO and Bartlett's test were measured to ensure the adequacy of the practices. Three CSF (3) were extracted for Soft TQM aspects while Seven (7) factors were extracted for LM practices. Results obtained from PCA indicated that Malaysian managers are involved with LM wastes, Kaizen, Just in Time, continuous flow, TPM, Workforce Management, standardized work practices, strategic planning and human aspects. The novelty of the present study stems from the realization of TQM and LM aspects that determine the priorities of Malaysian managers in manufacturing environment by providing guidelines about the most important factors to adopt.